Computational insights into magnetoelectric nanoparticles for neural stimulation - Vezzoni, Alessia; Chiaramello, Emma; Galletta, Valentina; Bonato, Marta; Parazzini, Marta; Fiocchi, Serena (Frontiers in Neuroscience, 2025)
IntroductionThis study investigates the potential of magnetoelectric nanoparticles (MENPs) as a novel tool for localized electric stimulation of the central nervous system at single-neuron level, addressing the need for precise and minimally invasive neural modulation.MethodsUsing a computational framework based on finite element methods coupled with neuronal dynamics simulations on a realistic model of a hippocampal CA1 pyramidal neuron, the study evaluates how MENPs' stimulation parameters influence neural activation. Analyses included electric potential distributions, the activating function along the axon, amplification coefficients required for action potential generation, spike propagation, and membrane potential. The study initially focused on highly localized stimulation using a nanometric MENP close to the axon and then demonstrated the feasibility of a more realistic framework involving a micrometric cluster of MENPs. To emulate physiological signal convergence, the summation effects of multiple MENPs strategically positioned across the basal dendritic tree near the axon were explored.Results and discussionThe findings revealed the critical role of MENPs' configuration, location, and modulating stimuli in shaping neuronal responses, highlighting the feasibility of MENPs as a cutting-edge approach for precise neural stimulation. This work provides a foundation for integrating MENPs into therapeutic strategies for neurodegenerative diseases.